Right To Property and Maintenance of Illegitimate Child Under Hindu Law - Hazarika, Rupa (International Journal of Membrane Science and Technology, 2024)
The concept of property is evolving from the days of adopting the law relating to property of Hindu people. The laws relating to property undergoes many changes from time to time as to accommodate the changing need of the society. The major changes in the law of property held after the adoption of our Constitution. The Article 14 of the Constitution of India guarantees equality among men and women as a fundamental right. Following by Article 15 which allows special provisions can be made for women and child. Article 19 1(f) which said that right to property was a fundamental right, which later on amended and now property is a legal right under article 300A of the Constitution of India. Article 39(f) which is directive principle also concern about the safeguard of the child. The court observed that right to property is not only a constitutional right but also a human right1, and no person can be deprived of his property save and except by and in accordance with law. Due to Constitutional guarantees the legislature has brought Hindu Succession Act in 19562 and Hindu Marriage Act in 19553 along with three other Acts. Hindu Succession Act has amended and codified the law relating to intestate succession4. This Act has laid down a uniform and comprehensive system of inheritance of property. Moreover this Act gave rights to women to property which were unknown till then. The provision of this Act in relation to property is clear for legitimate child, but is silent for illegitimate child. The paper will focus on the right of illegitimate progeny to maintenance from their parents as well as right of inheritance to their parents self acquired as well as ancestral property in a Hindu family.